K121Q polymorphism in the Ectonucleotide Pyrophosphatase/Phosphodiesterase 1 gene is associated with acute kidney rejection - Sortica, Denise Alves (2019)
The identification of risk factors for acute rejection (AR) may lead to strategies to improve success of kidney transplantation. Ectonucleotidases are ectoenzymes that hydrolyze extracellular nucleotides into nucleosides, modulating the purinergic signaling. Some members of the Ectonucleotidase family have been linked to transplant rejection processes. However, the association of Ectonucleotide Pyrophosphatase / Phosphodiesterase 1 (ENPP1) with AR has not yet been evaluated. The aim of this study was to evaluate the association between the K121Q polymorphism of ENPP1 gene and AR in kidney transplant patients. We analyzed 449 subjects without AR and 98 with AR from a retrospective cohort of kidney transplant patients from Southern Brazil. K121Q polymorphism was genotyped using allelic discrimination-real-time PCR. Cox regression analysis was used to evaluate freedom of AR in kidney transplant patients according to genotypes. Q allele frequency was 17.6% in recipients without AR and 21.9% in those with AR (P = 0.209). Genotype frequencies of the K121Q polymorphism were in Hardy-Weinberg equilibrium in non-AR patients (P = 0.70). The Q/Q genotype (recessive model) was associated with AR (HR = 2.83, 95% CI 1.08–7.45; P = 0.034) after adjusting for confounders factors. Our findings suggest a novel association between the ENPP1 121Q/Q genotype and AR in kidney transplant recipients.